ZSM-48 molecular sieve as well as preparation method and application thereof, hydrogen type ZSM-48 molecular sieve as well as preparation method and application thereof
By preparing nanosheet-shaped ZSM-48 molecular sieve and hydrogen-type ZSM-48 molecular sieve, the problems of large mass transfer diffusion resistance and poor catalytic performance are solved, and efficient catalytic performance and stability in organic matter conversion reaction are achieved.
Patent Information
- Application Number
- CN202310715991.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-15
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-06-15
AI Technical Summary
The existing ZSM-48 molecular sieve has the problem of large mass transfer and diffusion resistance, which affects the catalytic performance, and the catalytic performance of molecular sieves with high silicon-aluminum ratio and low silicon-aluminum ratio are poor.
Using nanosheet-shaped ZSM-48 molecular sieve and its preparation method, the nanosheet-shaped morphology formed by agglomeration of nanoparticles through the heating and crystallization treatment of mixed liquid containing silicon source, aluminum source, structural guide agent and alkali source, and the nanosheet-shaped morphology was formed by ammonium. The hydrogen-type ZSM-48 molecular sieve was exchanged to improve its catalytic performance.
The high catalytic performance and stability of nanosheet-shaped ZSM-48 molecular sieve was achieved, especially in the organic matter conversion reaction, which showed a good catalytic effect, reducing the mass transfer diffusion resistance.
Smart Images

Figure CN119143149A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of molecular sieves, and in particular to a ZSM-48 molecular sieve and a preparation method and application thereof, and a hydrogen-type ZSM-48 molecular sieve and a preparation method and application thereof. Background Art
[0002] ZSM-48 molecular sieve has a one-dimensional channel structure with ten-membered ring pores, and is often used as a catalyst in organic compound conversion reactions such as aromatic alkylation, isomerization, disproportionation, and methanol conversion. Currently, there are ZSM-48 molecular sieves with high silicon-aluminum ratios (usually higher than 100) and low silicon-aluminum ratios (for example, 30), but both high silicon-aluminum ratio and low silicon-aluminum ratio ZSM-48 molecular sieves have poor catalytic performance.
[0003] Zhu et al. synthesized a high-crystallinity aluminum-rich ZSM-48 molecular sieve by allyl dimethyl ammonium chloride (ATMA), which has high activity in catalyzing the hydroisomerization reaction of n-heptane, but there are problems such as large amount of structure-directing agent and high cost [Kake Zhu, and Xinggui Zhou et al., Ind. Eng. Chem. Res. 2020, 59, 11139-11148]. However, the molecular sieve synthesized by the above method has large mass transfer and diffusion resistance, which affects the catalytic performance. Daou et al. reported the use of (C 22 H 45 N + (CH3)2C6H 12 N + (CH3)2CH2C6H4CH2N + (CH3)2C6H 12 N + (CH3)2C 22 H 45 )(Br - )2(Cl - )2 synthesized a multi-level structure ZSM-48 molecular sieve with a silicon-aluminum ratio of 31, but the low crystallinity of the product and the existence of competitive phase problems limited its application [T.Jean Daou, New J.Chem., 2018, 42, 4457]. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem of large mass transfer and diffusion resistance of ZSM-48 molecular sieve in the prior art, which affects the catalytic performance, and to provide a ZSM-48 molecular sieve and a preparation method and application thereof, a hydrogen-type ZSM-48 molecular sieve and a preparation method and application thereof. The molecular sieve has a nano-sheet morphology, can be used as an adsorbent or a catalyst for organic compound conversion, and has good molecular diffusion.
[0005] A first aspect of the present invention provides a nano-sheet ZSM-48 molecular sieve, wherein the molecular sieve has a nano-sheet morphology formed by agglomeration of nanoparticles, the length of the nanoparticles is not higher than 50 nm, and the length of the nanosheet is not higher than 1000 nm.
[0006] The second aspect of the present invention provides a method for preparing the ZSM-48 molecular sieve described in the first aspect, wherein the preparation method comprises: heating and crystallizing a mixed solution formed by a silicon source, an aluminum source, a structure directing agent and an alkali source raw material; the structure directing agent is composed of a structural unit a represented by formula (1),
[0007]
[0008] In formula (1), X is halogen or OH, and * represents a bonding site.
[0009] The third aspect of the present invention provides the use of the ZSM-48 molecular sieve described in the first aspect of the present invention in adsorption treatment and / or organic compound conversion reaction.
[0010] The fourth aspect of the present invention provides a method for preparing a hydrogen-type ZSM-48 molecular sieve, wherein the preparation method comprises: subjecting the ZSM-48 molecular sieve described in the first aspect of the present invention to ammonium exchange and solid-liquid separation and then heat treatment to obtain the hydrogen-type ZSM-48 molecular sieve.
[0011] The fifth aspect of the present invention provides a hydrogen-type ZSM-48 molecular sieve prepared by the preparation method in the third aspect of the present invention.
[0012] The sixth aspect of the present invention provides the use of the hydrogen-type ZSM-48 molecular sieve described in the fifth aspect of the present invention in adsorption treatment and / or organic compound conversion reaction.
[0013] Compared with the prior art, the present invention has at least the following beneficial effects:
[0014] The ZSM-48 molecular sieve of the invention has a nano-sheet morphology formed by agglomeration of nano-particles, a special crystal morphology, good accessibility, and good catalytic performance in organic matter conversion reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is the X-ray diffraction pattern of the molecular sieve sample in Example 1;
[0016] Figure 2 is the SEM image of the molecular sieve sample in Example 1 at different magnifications;
[0017] Figure 3 is the N2 physical adsorption diagram of the molecular sieve sample in Example 1;
[0018] Figure 4 is the NH3-TPD diagram of the hydrogen-type ZSM-48 molecular sieve sample in Example 1;
[0019] Figure 5 is the X-ray diffraction pattern of the molecular sieve sample in Example 2;
[0020] Figure 6 is the SEM image of the molecular sieve sample in Example 2 at different magnifications;
[0021] Figure 7 is the X-ray diffraction pattern of the molecular sieve sample in Example 5;
[0022] Figure 8 is the SEM image of the molecular sieve sample in Example 5 at different magnifications;
[0023] Fig. 9 This is the SEM image of the molecular sieve sample in Comparative Example 1. DETAILED DESCRIPTION
[0024] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0025] A first aspect of the present invention provides a nano-sheet ZSM-48 molecular sieve, wherein the molecular sieve has a nano-sheet morphology formed by agglomeration of nanoparticles, the length of the nanoparticles is not higher than 50 nm, and the length of the nanosheet is not higher than 1000 nm.
[0026] In the present invention, the ZSM-48 molecular sieve has a specific nano-sheet morphology, wherein the length of the nanoparticles is not higher than 50 nm and the length of the nanosheets is not higher than 1000 nm. This makes the ZSM-48 molecular sieve highly accessible and has good catalytic performance in organic matter conversion reactions.
[0027] According to the present invention, in some preferred embodiments, the length of the nanoparticles is 10-50 nm, for example, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm, preferably 15-45 nm. The molecular sieve of the aforementioned embodiment has a smaller diffusion resistance.
[0028] According to the present invention, in some embodiments, the molecular sieve has a morphology of intersecting nanosheets. The molecular sieve of the aforementioned embodiment has better molecular diffusivity, adsorption and stability.
[0029] According to the present invention, in some embodiments, the nanosheets are elliptical nanosheets. The molecular sieves of the aforementioned embodiments have a better short axis structure and have better catalytic performance and stability in organic matter conversion reactions.
[0030] According to the present invention, in some preferred embodiments, the length of the nanosheet is 300-900nm, for example 300nm, 370nm, 400nm, 430nm, 460nm, 510nm, 550nm, 600nm, 620nm, 650nm, 700nm, 750nm, 800nm or 900nm, preferably 300-800nm. The molecular sieve of the aforementioned embodiment has better molecular diffusivity and has better catalytic performance when used in organic matter conversion reactions.
[0031] According to the present invention, in some preferred embodiments, the thickness of the nanosheet is 10-100 nm, such as 10 nm, 16 nm, 18 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, preferably 10-80 nm. The molecular sieve of the aforementioned embodiment has better stability and molecular diffusivity.
[0032] According to the present invention, in some preferred embodiments, the width of the nanosheet is 200-800nm, such as 200nm, 250nm, 280nm, 300nm, 320nm, 360nm, 400nm, 440nm, 460nm, 490nm, 530nm, 600nm, 700nm or 800nm, preferably 200-700nm. The molecular sieve of the aforementioned embodiment has better molecular diffusivity and better catalytic performance when used.
[0033] According to the present invention, in some preferred embodiments, the aspect ratio of the nanosheet is 1-2, such as 1, 1.1, 1.2, 1.3, 1.4, 1.6, 1.7, 1.8, 1.9 or 2, preferably 1.1-1.9. The molecular sieve of the aforementioned embodiment has lower diffusion resistance, so that its catalytic performance is better.
[0034] According to the present invention, in some preferred embodiments, the aspect ratio of the nanosheet is 5-30, such as 5, 8, 10, 15.7, 17, 23, 24, 25, 28 or 30, preferably 5-25. The molecular sieve of the aforementioned embodiment has better molecular diffusivity and better catalytic performance when used.
[0035] According to the present invention, as long as the purpose of the present invention can be achieved, the silicon-aluminum ratio of the molecular sieve is not particularly limited. In some embodiments, the SiO2 / Al2O3 molar ratio of the molecular sieve is 40-250, such as 40, 44, 47, 53, 56, 65, 79, 84, 100, 131, 160, 171, 195, 210, 240 or 250, preferably 50-240. The molecular sieve with special morphology in the present invention has a wider molecular sieve silicon-aluminum ratio under the aforementioned embodiment, and the accessibility of the molecular sieve is better.
[0036] According to the present invention, as long as the present invention can be achieved, the specific surface area of the molecular sieve is not particularly limited. In some embodiments, the total specific surface area of the molecular sieve is not less than 300 m 2 / g. The molecular sieve with special morphology in the present invention has a wider total specific surface area under the above-mentioned embodiment, and the above-mentioned molecular sieve has better catalytic performance.
[0037] According to the present invention, in some preferred embodiments, the total specific surface area of the molecular sieve is 300-500 m 2 / g, e.g. 300 m 2 / g, 312m 2 / g, 321m 2 / g, 326m 2 / g, 330m 2 / g, 335m 2 / g, 346m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g or 500m 2 / g. The molecular sieve of the above embodiment has better accessibility and better catalytic performance in organic matter conversion reaction.
[0038] According to the present invention, in some embodiments, the external specific surface area of the molecular sieve is not less than 100 m 2 / g. The molecular sieve of the aforementioned embodiment has better catalytic performance.
[0039] According to the present invention, in some preferred embodiments, the external specific surface area of the molecular sieve is 100-250 m 2 / g, e.g. 100 m 2 / g, 120m 2 / g, 146m 2 / g, 150m 2 / g, 156m 2 / g, 159m 2 / g, 162m 2 / g, 174m 2 / g, 177m 2 / g, 180m 2 / g, 190m 2 / g, 200m 2 / g, 210m 2 / g, 220m 2 / g, 240m 2 / g or 250m 2 / g. The molecular sieve of the aforementioned embodiment has better catalytic performance and stability.
[0040] According to the present invention, the molecular sieve of the specific morphology of the present invention has abundant mesopores. As long as the purpose of the present invention can be achieved, the total pore volume of the molecular sieve is not particularly limited. In some embodiments, the total pore volume of the molecular sieve is not less than 0.25 cm 3 / g. The molecular sieve of the aforementioned embodiment has better adsorption and dispersibility.
[0041] According to the present invention, in some preferred embodiments, the total pore volume of the molecular sieve is 0.25-0.6 cm 3 / g, e.g. 0.25 cm 3 / g, 0.3 cm 3 / g, 0.35 cm 3 / g, 0.37 cm 3 / g, 0.39 cm 3 / g, 0.4 cm 3 / g, 0.41 cm 3 / g, 0.42 cm 3 / g, 0.45 cm 3 / g, 0.5 cm 3 / g, 0.55 cm 3 / g, 0.6 cm 3 The molecular sieve of the aforementioned embodiment has abundant mesopores, and has good catalytic performance when used for organic matter conversion reaction.
[0042] According to the present invention, as long as the purpose of the present invention can be achieved, the micropore volume of the molecular sieve is not particularly limited. In some embodiments, the micropore volume of the molecular sieve is not less than 0.05 cm 3 The molecular sieve of the aforementioned embodiment has abundant mesopores, and has good catalytic performance when used for organic matter conversion reaction.
[0043] According to the present invention, in some preferred embodiments, the micropore volume of the molecular sieve is 0.05-0.2 cm 3 / g, e.g. 0.05 cm 3 / g, 0.06 cm 3 / g, 0.07 cm 3 / g, 0.08 cm 3 / g, 0.1 cm 3 / g, 0.12 cm 3 / g, 0.15 cm 3 / g, 0.18 cm 3 / g or 0.2 cm 3 / g. The molecular sieve of the aforementioned embodiment has better catalytic performance in organic matter conversion reaction.
[0044] The second aspect of the present invention provides a method for preparing the ZSM-48 molecular sieve described in the first aspect, wherein the preparation method comprises: heating and crystallizing a mixed solution formed by a silicon source, an aluminum source, a structure directing agent and an alkali source raw material; the structure directing agent is composed of a structural unit a represented by formula (1),
[0045]
[0046] In formula (1), X is halogen or OH, and * represents a bonding site.
[0047] In the present invention, the ZSM-48 molecular sieve prepared by using the structural unit a shown in formula (1) to constitute a structure directing agent has a special morphology and high crystallinity, abundant mesopores and adjustable acid density, the molecular sieve has good accessibility, and has good catalytic performance in organic matter conversion reactions. The inventors have studied and speculated that: on the one hand, the methylene chain length in the structural unit a in the present invention can regulate the connectivity between micropores and mesopores; on the other hand, the positive charge density of the cation in the structural unit a can enable the structure directing agent to balance the negative charge of the Al position on the aluminum-rich molecular sieve skeleton, and at the same time, the specific methylene chain length and side chain structure can change the positive charge density of the cation in the structural unit a, so that the molecular sieve has better accessibility and has good catalytic performance in organic matter conversion reactions.
[0048] In the present invention, the structure directing agent may exist in the form of a pure substance or in the form of a mixture, wherein "pure substance" means that the structure directing agent is composed of structure directing agents with the same degree of polymerization, and "mixture" means that the structure directing agent is composed of structure directing agents with different degrees of polymerization. The present invention has no special restrictions on the composition form of the structure directing agent. In the present invention, the number of structural units a is represented by the average degree of polymerization.
[0049] According to the present invention, in some embodiments, the average degree of polymerization of the structure directing agent is 2-20, for example, 2, 3, 3.2, 4, 5.3, 8, 10, 11.1, 12, 14, 16, 18 or 20, preferably 3- 12. Using the above embodiment, the prepared molecular sieve has high crystallinity, abundant mesopores and adjustable acid density.
[0050] In the present invention, the mixed liquid formed by raw materials containing silicon source, aluminum source, structure directing agent and alkali source refers to a mixture obtained by mixing a solvent (such as water) with raw materials such as silicon source, aluminum source, structure directing agent and alkali source; it can also be a mixture obtained by mixing raw materials such as silicon source, aluminum source, solution containing structure directing agent (such as a solution obtained by mixing solvent water and structure directing agent), solution containing alkali source (such as a solution obtained by mixing solvent water and alkali source), and the mixing method is conventional in the art, for example, stirring at room temperature for 12-36 hours.
[0051] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of each raw material in the aqueous solution is not particularly limited. In some embodiments, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, the structure directing agent is calculated as structural unit a, and the alkali source is calculated as cation. The molar ratio of the silicon source, the aluminum source, the structure directing agent, the alkali source and the water in the mixture is 1:a:b:c:d, wherein a is 0.004-0.03, b is 0.03-0.1, c is 0.10-0.5, and d is 8-100. Using the above embodiment, the synthesized molecular sieve has a wide range of silicon-aluminum ratios.
[0052] According to the present invention, in some preferred embodiments, a is 0.004-0.025. By adopting the above embodiment, a ZSM-48 molecular sieve with good polarity can be formed better.
[0053] According to the present invention, in some preferred embodiments, b is 0.04-0.09. By adopting the above-mentioned embodiment, a ZSM-48 molecular sieve with a specific morphology can be better formed, and the synthesized molecular sieve has better catalytic performance.
[0054] According to the present invention, in some preferred embodiments, c is 0.15-0.45. The above embodiments can further promote crystallization and better form ZSM-48 molecular sieve.
[0055] According to the present invention, in some preferred embodiments, d is 10 to 90. The above embodiments can better promote the crystallization process.
[0056] According to the present invention, those skilled in the art will understand that a silicon source refers to a substance that provides silicon elements. As long as the purpose of the present invention can be achieved, the specific type of the silicon source is not particularly limited. In some embodiments, the silicon source is selected from at least one of tetraethyl orthosilicate, fumed silica, silica sol and white carbon black.
[0057] According to the present invention, those skilled in the art can understand that an aluminum source refers to a substance that provides aluminum elements. As long as the purpose of the present invention can be achieved, the specific type of the aluminum source is not particularly limited. In some embodiments, the aluminum source is selected from at least one of aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum hydroxide, sodium aluminate, pseudo-boehmite and aluminum isopropoxide.
[0058] According to the present invention, those skilled in the art will understand that the alkali source refers to a substance that provides alkali metal elements. As long as the purpose of the present invention can be achieved, the specific type of the alkali source is not particularly limited. In some embodiments, the alkali source is selected from at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide.
[0059] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions of the crystallization treatment are not limited. In some embodiments, the conditions of the crystallization treatment include: crystallization at 130-190° C. for 2-14 days.
[0060] According to the present invention, in some preferred embodiments, the conditions of the crystallization treatment include: crystallization at 140-180° C. for 3-12 days.
[0061] According to the present invention, the crystallization process can be static crystallization or dynamic crystallization (for example, under stirring at 40-100 rpm) according to the needs.
[0062] According to the present invention, when preparing ZSM-48 molecular sieve, a post-treatment method can be selected as needed after the crystallization treatment. In some embodiments, solid-liquid separation and heat treatment are performed after the crystallization treatment.
[0063] According to the present invention, solid-liquid separation refers to obtaining a solid from the mixture obtained by crystallization treatment by any conventionally known separation method, and the separation methods that can be listed are filtration and washing; filtration can be simple suction filtration or other filtration methods, and washing can be performed using deionized water and / or ethanol.
[0064] According to the present invention, in some embodiments, the heat treatment conditions include: calcination after drying.
[0065] According to the present invention, drying can be carried out according to conventional drying methods in the art, such as drying at 40-250° C. for 8-30 hours, preferably drying at 60-150° C. for 10-20 hours, wherein the drying can be carried out under normal pressure or under reduced pressure.
[0066] According to the present invention, as long as the purpose of the present invention can be achieved, the calcination can be carried out in any manner conventionally known in the art. In some embodiments, the calcination conditions include: a calcination temperature of 300-800°C, preferably 400-650°C.
[0067] According to the present invention, in some embodiments, the calcination conditions include: the calcination time is 1-10 hours, preferably 3-6 hours.
[0068] According to the present invention, in some embodiments, the calcination conditions include: performing the calcination in an oxygen-containing atmosphere.
[0069] In the present invention, the oxygen-containing atmosphere refers to air or an oxygen atmosphere.
[0070] The third aspect of the present invention provides the use of the ZSM-48 molecular sieve described in the first aspect of the present invention in adsorption treatment and / or organic compound conversion reaction.
[0071] In the present invention, the ZSM-48 molecular sieve with special morphology has good accessibility and good catalytic performance in organic matter conversion reaction.
[0072] In the present invention, the organic compound conversion reaction generally involves reactions such as Friedel-Crafts alkylation reaction, isomerization reaction, hydroisomerization reaction, hydrogenolysis reaction, and the like.
[0073] In the present invention, the ZSM-48 molecular sieve can be used in any physical form, such as powder, granular, or kneaded with a conventional binder in the art to form a molded product (such as strips, clover, etc.). These physical forms can be obtained in any conventional manner known in the art, and the present invention has no particular limitation thereto; the ZSM-48 molecular sieve can also be used after being modified according to conventional modification methods in the art, such as exchanging the molecular sieve with ammonium to form a hydrogen-type ZSM-48 molecular sieve.
[0074] The fourth aspect of the present invention provides a method for preparing a hydrogen-type ZSM-48 molecular sieve, wherein the preparation method comprises: subjecting the ZSM-48 molecular sieve described in the first aspect of the present invention to ammonium exchange and solid-liquid separation and then heat treatment to obtain the hydrogen-type ZSM-48 molecular sieve.
[0075] In the present invention, the hydrogen-type ZSM-48 molecular sieve after ammonium exchange can maintain the special morphology of the ZSM-48 molecular sieve and its surface area and pore volume and other characteristics. The ZSM-48 molecular sieve is only converted into the hydrogen-type ZSM-48 molecular sieve, which brings about a change in the acid content on the basis of the ZSM-48 molecular sieve. In the heat treatment process after ammonium exchange and solid-liquid separation, the proton (H + ) replaces the alkali metal in the ZSM-48 molecular sieve, and the hydrogen-type ZSM-48 molecular sieve prepared by the ZSM-48 molecular sieve of the present invention has good catalytic performance and adsorption performance.
[0076] In the present invention, ammonium exchange is a conventional operation method in the art, that is, ammonium exchange is performed using an ammonium salt aqueous solution, the ammonium salt aqueous solution can be selected as needed, for example, the ammonium salt is selected from at least one of ammonium chloride, ammonium nitrate, ammonium carbonate and ammonium sulfate, and the ammonium ion concentration in the ammonium salt aqueous solution is 0.1-1 mol / L; the amount of the ammonium salt aqueous solution can be selected as needed, for example, the solid-liquid ratio of ZSM-48 molecular sieve to the ammonium salt aqueous solution is 1: (5-20) (mass ratio); the conditions for ammonium exchange can be selected as needed, for example, ion exchange at 30-80° C. for 1-8h.
[0077] In the present invention, those skilled in the art can select the number of ammonium exchange and solid-liquid separation as needed, for example, 1-3 times.
[0078] According to the present invention, in the preparation of hydrogen-type ZSM-48 molecular sieve, the heat treatment includes conventional drying and calcination steps in the art, such as drying at 60-150°C overnight (the overnight drying time is generally 8-15 hours), and calcining at 400-650°C for 3-6 hours in an oxygen-containing atmosphere (such as an air atmosphere or an oxygen atmosphere).
[0079] The fifth aspect of the present invention provides a hydrogen-type ZSM-48 molecular sieve prepared by the preparation method in the third aspect of the present invention.
[0080] In the present invention, the hydrogen-type ZSM-48 molecular sieve has good adsorption properties and has good catalytic performance when used in organic matter conversion reactions.
[0081] According to the present invention, in some embodiments, the total acid content of the hydrogen-type ZSM-48 molecular sieve is not less than 150 μmol / g. The molecular sieve of the aforementioned embodiment has better activity and catalytic performance.
[0082] According to the present invention, in some preferred embodiments, the total acid amount of the hydrogen ZSM-48 molecular sieve is 150-1000 μmol / g, for example, 150 μmol / g, 189 μmol / g, 250 μmol / g, 326 μmol / g, 400 μmol / g, 500 μmol / g, 575 μmol / g, 596 μmol / g, 686 μmol / g, 700 μmol / g, 724 μmol / g, 812 μmol / g, 900 μmol / g or 1000 μmol / g. The molecular sieve of the aforementioned embodiment has good accessibility and has good catalytic performance for organic conversion reactions.
[0083] According to the present invention, in some embodiments, the strong acid content of the hydrogen-type ZSM-48 molecular sieve is not less than 70 μmol / g. The molecular sieve of the aforementioned embodiment has better catalytic performance.
[0084] According to the present invention, in some preferred embodiments, the strong acid amount of the molecular sieve is 70-500 μmol / g, for example, 70 μmol / g, 77 μmol / g, 84 μmol / g, 150 μmol / g, 186 μmol / g, 247 μmol / g, 261 μmol / g, 284 μmol / g, 308 μmol / g, 328 μmol / g, 400 μmol / g or 500 μmol / g. The molecular sieve of the aforementioned embodiment has better catalytic performance.
[0085] According to the present invention, in some embodiments, the proportion of the strong acid content of the hydrogen-type ZSM-48 molecular sieve to the total acid content is not less than 25%. The molecular sieve of the aforementioned embodiment has good catalytic properties.
[0086] According to the present invention, in some preferred embodiments, the ratio of the strong acid content of the molecular sieve to the total acid content is 25-50%, for example, 25%, 26%, 31%, 32%, 38%, 39%, 41%, 43%, 45% or 50%. The molecular sieve machine compound conversion catalyst of the aforementioned embodiment has good catalytic performance and the target product has good selectivity.
[0087] The sixth aspect of the present invention provides the use of the hydrogen-type ZSM-48 molecular sieve described in the fifth aspect of the present invention in adsorption treatment and / or organic compound conversion reaction.
[0088] In the present invention, the structure of the nano-sheet ZSM-48 molecular sieve is determined by an X-ray diffraction spectrum (XRD), and the X-ray diffraction spectrum (XRD) is measured by an X-ray powder diffractometer. Before the sample test, a scanning electron microscope (SEM) is used to observe the crystallization of the molecular sieve sample to confirm that the sample contains only one crystal, that is, the molecular sieve sample is a pure phase, and then an XRD test is performed on this basis to ensure that there are no interference peaks of other crystals in the diffraction peaks in the XRD spectrum.
[0089] In the present invention, the molecular sieve X-ray powder diffractometer model is D / MAX2550VB / PC of Rigaku Company of Japan, and the phase of the sample is analyzed. The CuKα ray source is Nickel filter, 2θ scanning range 5-50°, operating voltage 40KV, current 40mA, scanning rate 10° / min.
[0090] In the present invention, the model of the molecular sieve scanning electron microscope (SEM) is NOVA NanoSEM 450 field emission scanning electron microscope of FEI Company of the United States. The molecular sieve is observed at different magnifications using the scanning electron microscope, an observation field of view is randomly selected, the length of the nanoparticles in the observation field of view is calculated, the operation is repeated for a total of 10 times, the average value of the sum of 10 times is used as the length of the nanoparticles, and the average value of the length of all nanosheets is calculated, the operation is repeated for a total of 10 times, the average value of the sum of 10 times is used as the length of the nanosheets, the width and thickness of all nanosheets in the observation field of view are measured by the same method, and the operation is repeated 5 times; wherein, the length of the nanoparticle is the maximum outer diameter of the particle; the length of the nanosheet is the maximum outer diameter of the nanosheet, the minimum diameter in the cross section with the largest area in the cross section perpendicular to the nanosheet is its thickness, and the maximum diameter is its width.
[0091] In the present invention, the total pore volume, micropore volume, total specific surface area and external specific surface area of the molecular sieve are measured by nitrogen physical adsorption and desorption method (BET method): the nitrogen physical adsorption and desorption isotherm of the molecular sieve is measured by a physical adsorption instrument (Beishide Instrument Technology (Beijing) Co., Ltd. 3H-2000PS4 model), and then calculated by the BET equation and t-plot equation. The experimental conditions for the molecular sieve are: the measurement temperature is -196°C, and the molecular sieve is heat-treated at 550°C in air atmosphere for 6 hours before measurement, and then pre-treated at 350°C in vacuum for 4 hours.
[0092] In the present invention, the SiO2 / Al2O3 molar ratio of the molecular sieve is tested by an inductively coupled plasma atomic emission spectrometer (ICP) (model: Varian 710-ES) of the molecular sieve, and the analysis sample is dissolved in hydrofluoric acid to detect the content of the element in moles.
[0093] In the present invention, the acid content of the molecular sieve is measured by NH3-TPD chemical adsorption-desorption curve using Micrometer Chemisorb 2720 instrument. Before the test, the sample is activated at 550°C for 1 hour, ammonia is adsorbed at 100°C for 20 minutes, and then desorption is detected at 100-600°C. The peak area is quantified by quantitative ring pulse ammonia, and the peak is separated by Gaussian distribution. The acid content corresponding to the desorption temperature above 300°C can be considered as the acid content of strong acid.
[0094] The present invention will be described in detail below by way of examples. In the following examples:
[0095] The structure directing agent is composed of the structural unit a shown in formula (1),
[0096]
[0097] In formula (1), * represents a linking site.
[0098] In the following examples and comparative examples:
[0099] The conditions for the hydroisomerization of n-heptane are: catalyst loading of 0.4 g, particle size of 20-40 mesh, hydrogen to n-heptane molar ratio of 26, reaction temperature of 200-400°C, weight hourly space velocity of 1 h -1 The highest yield of the isomer product obtained as the reaction time is measured is the isomer yield.
[0100] Yield of isomers % = (mass of isomers in the product) / (total mass of carbon-containing products) × 100%;
[0101] The isomer products are single-branched alkanes and double-branched alkane isomers, and the carbon-containing by-products are mainly cracking products, wherein the raw material n-heptane is not included in the products.
[0102] Example 1
[0103] 4.60 g of deionized water, 0.14 g of a structure directing agent (X is Br, average degree of polymerization is 3.2), 0.08 g of aluminum nitrate nonahydrate, 0.09 g of sodium hydroxide, and 1.35 g of ethyl orthosilicate were stirred at room temperature for 24 hours to obtain a mixture. The final molar ratio of the mixture was:
[0104] SiO2 / Al2O3=61;
[0105] NaOH / SiO2=0.35;
[0106] SDA / SiO2=0.05;
[0107] H2O / SiO2=40;
[0108] The final mixture was charged into a stainless steel reactor and heated for crystallization at 150°C for 5 days under static crystallization conditions. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0109] Figure 1 is the X-ray diffraction pattern of the molecular sieve sample. Figure 1 The molecular sieve sample that can be obtained is ZSM-48 molecular sieve;
[0110] Figure 2 The SEM images of the molecular sieve samples at different magnifications are shown in Figure 2. Figure 2It can be obtained that the molecular sieve sample has an elliptical nanosheet morphology formed by the aggregation of nanoparticles, and the specific nanosheet cross morphology, the length of the nanoparticle is 35nm, the thickness of the nanosheet is 30nm, the length is 700nm, the width is 440nm, the aspect ratio is 23.3, and the aspect ratio is 1.6;
[0111] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was 47 measured by inductively coupled plasma atomic emission spectroscopy (ICP);
[0112] The N2 physical adsorption diagram of the molecular sieve sample is as follows Figure 3 As shown, the specific surface area of the molecular sieve is 330 m 2 / g, the external specific surface area measured by BET method is 180 m 2 / g; total pore volume 0.41 cm 3 / g, micropore volume is 0.06 cm 3 / gram.
[0113] The molecular sieve sample was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for 3 hours, centrifuged and washed, and the above steps were repeated twice, then dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain hydrogen-type ZSM-48 molecular sieve;
[0114] The NH3-TPD diagram of hydrogen-type ZSM-48 molecular sieve is as follows Figure 4 As shown, it can be obtained that the total acid content of the molecular sieve sample is 793 μmol / g, the strong acid content is 328 μmol / g, and the proportion of the strong acid content to the total acid content is 41%.
[0115] Hydroisomerization reaction was carried out using hydrogen-type ZSM-48 molecular sieve, the catalyst loading was 0.4 g, the particle size was 20-40 mesh, the molar ratio of hydrogen to n-heptane was 26, the reaction temperature was 200-400 °C, and the weight hourly space velocity was 1 h -1 In the temperature range of 280-320°C, the yield of the isomer product reached a maximum of 71%.
[0116] Example 2
[0117] 17.20 g of deionized water, 0.52 g of a structure directing agent (X is Br, average degree of polymerization is 3.2), 0.32 g of sodium hydroxide, 0.18 g of aluminum nitrate nonahydrate, and 5.10 g of ethyl orthosilicate were stirred at room temperature for 24 hours to obtain a mixture. The final molar ratio of the mixture was:
[0118] SiO2 / Al2O3=102;
[0119] NaOH / SiO2=0.33;
[0120] SDA / SiO2=0.05;
[0121] H2O / SiO2=39;
[0122] The final mixture was charged into a stainless steel reactor and heated for crystallization at 170°C dynamic (60rpm) conditions for 3 days. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0123] Figure 5 is the X-ray diffraction pattern of the molecular sieve sample. Figure 5 The molecular sieve sample that can be obtained is ZSM-48 molecular sieve;
[0124] Figure 6 The SEM images of the molecular sieve samples at different magnifications are shown in Figure 2. Figure 6 It can be obtained that the molecular sieve sample has an elliptical nanosheet morphology formed by the aggregation of nanoparticles, and the specific nanosheet cross morphology, the length of the nanoparticle is 40nm, the thickness of the nanosheet is 25nm, the length is 600nm, the width is 490nm, the aspect ratio is 24.0, and the aspect ratio is 1.2;
[0125] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was measured to be 84 by inductively coupled plasma atomic emission spectroscopy (ICP);
[0126] N2 physical adsorption diagram of molecular sieve samples and Figure 3 Similarly, the specific surface area of molecular sieve is 346 m 2 / g, the external specific surface area measured by BET method is 174 m 2 / g; total pore volume 0.39 cm 3 / g, micropore volume is 0.07 cm 3 / gram.
[0127] The molecular sieve sample was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for 3 hours, centrifuged and washed, and the above steps were repeated twice, then dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain hydrogen-type ZSM-48 molecular sieve;
[0128] NH3-TPD diagram of hydrogen-type ZSM-48 molecular sieve Figure 4 Similarly, it can be obtained that the total acid content of the molecular sieve sample is 575 μmol / g, the strong acid content is 247 μmol / g, and the proportion of the strong acid content to the total acid content is 43%.
[0129] Hydroisomerization reaction was carried out using hydrogen-type ZSM-48 molecular sieve, the catalyst loading was 0.4 g, the particle size was 20-40 mesh, the molar ratio of hydrogen to n-heptane was 26, the reaction temperature was 200-400 °C, and the weight hourly space velocity was 1 h -1 In the temperature range of 280-320°C, the yield of the isomer product reaches a maximum of 70%.
[0130] Example 3
[0131] 4.50 g of deionized water, 0.16 g of a structure directing agent aqueous solution (X is OH, the average degree of polymerization is 3.2, and the mass concentration is 60%), 0.08 g of sodium hydroxide, 0.08 g of aluminum nitrate nonahydrate, and 1.35 g of ethyl orthosilicate were stirred at room temperature for 24 hours to obtain a mixture. The final molar ratio of the mixture was:
[0132] SiO2 / Al2O3=61;
[0133] NaOH / SiO2=0.31;
[0134] SDA / SiO2=0.05;
[0135] H2O / SiO2=39;
[0136] The final mixture was charged into a stainless steel reactor and heated for crystallization at 150°C for 6 days under static crystallization conditions. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0137] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample can be obtained as ZSM-48 molecular sieve;
[0138] SEM images of molecular sieve samples and Figure 2 Similarly, it can be obtained that the molecular sieve sample has an elliptical nanosheet morphology formed by the aggregation of nanoparticles, and the specific nanosheet cross morphology, the length of the nanoparticle is 25nm, the thickness of the nanosheet is 35nm, the length is 550nm, the width is 300nm, the aspect ratio is 15.7, and the aspect ratio is 1.8;
[0139] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was measured to be 56 by inductively coupled plasma atomic emission spectroscopy (ICP);
[0140] N2 physical adsorption diagram of molecular sieve samples and Figure 3 Similarly, the specific surface area of molecular sieve is 326 m 2 / g, the external specific surface area measured by BET method is 177 m 2 / g; total pore volume 0.38 cm3 / g, micropore volume is 0.07 cm 3 / gram.
[0141] The molecular sieve sample was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for 3 hours, centrifuged and washed, and the above steps were repeated twice, then dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain hydrogen-type ZSM-48 molecular sieve;
[0142] NH3-TPD diagram of hydrogen-type ZSM-48 molecular sieve Figure 4 Similarly, it can be obtained that the total acid content of the molecular sieve sample is 686 μmol / g, the strong acid content is 261 μmol / g, and the proportion of the strong acid content to the total acid content is 38%.
[0143] Hydroisomerization reaction was carried out using hydrogen-type ZSM-48 molecular sieve, the catalyst loading was 0.4 g, the particle size was 20-40 mesh, the molar ratio of hydrogen to n-heptane was 26, the reaction temperature was 200-400 °C, and the weight hourly space velocity was 1 h -1 In the temperature range of 280-320°C, the yield of the isomer product reaches a maximum of 70%.
[0144] Example 4
[0145] 5.20 g of deionized water, 0.25 g of a structure directing agent aqueous solution (X is OH, the average degree of polymerization is 5.3, and the mass concentration is 60%), 0.10 g of sodium hydroxide, 0.02 g of sodium aluminate, and 1.50 g of tetraethyl orthosilicate were stirred at room temperature for 24 hours to obtain a mixture. The final molar ratio of the mixture was:
[0146] SiO2 / Al2O3=59;
[0147] NaOH / SiO2=0.38;
[0148] SDA / SiO2=0.07;
[0149] H2O / SiO2=41;
[0150] The final mixture was charged into a stainless steel reactor and heated for crystallization at 160°C for 4 days under static crystallization conditions. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0151] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample can be obtained as ZSM-48 molecular sieve;
[0152] SEM images of molecular sieve samples and Figure 2Similarly, it can be obtained that the molecular sieve sample has an elliptical nanosheet morphology formed by the aggregation of nanoparticles, and the specific nanosheet cross morphology, the length of the nanoparticle is 30nm, the thickness of the nanosheet is 30nm, the length is 510nm, the width is 360nm, the aspect ratio is 17.0, and the aspect ratio is 1.4;
[0153] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was measured to be 53 by inductively coupled plasma atomic emission spectroscopy (ICP);
[0154] N2 physical adsorption diagram of molecular sieve samples and Figure 3 Similarly, the specific surface area of molecular sieve is 335 m 2 / g, the external specific surface area measured by BET method is 162 m 2 / g; total pore volume 0.35 cm 3 / g, micropore volume is 0.07 cm 3 / gram.
[0155] The molecular sieve sample was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for 3 hours, centrifuged and washed, and the above steps were repeated twice, then dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain hydrogen-type ZSM-48 molecular sieve;
[0156] NH3-TPD diagram of hydrogen-type ZSM-48 molecular sieve Figure 4 Similarly, it can be obtained that the total acid content of the molecular sieve sample is 724 μmol / g, the strong acid content is 284 μmol / g, and the proportion of the strong acid content to the total acid content is 39%.
[0157] Hydroisomerization reaction was carried out using hydrogen-type ZSM-48 molecular sieve, the catalyst loading was 0.4 g, the particle size was 20-40 mesh, the molar ratio of hydrogen to n-heptane was 26, the reaction temperature was 200-400 °C, and the weight hourly space velocity was 1 h -1 In the temperature range of 280-320°C, the yield of the isomer product reached a maximum of 66%.
[0158] Example 5
[0159] 9.20 g of deionized water, 0.28 g of a structure directing agent (X is Br, average degree of polymerization is 11.1), 0.048 g of aluminum nitrate nonahydrate, 0.18 g of sodium hydroxide, and 2.70 g of ethyl orthosilicate were stirred at room temperature for 24 hours to obtain a mixture. The final molar ratio of the mixture was:
[0160] SiO2 / Al2O3=203;
[0161] NaOH / SiO2=0.35;
[0162] SDA / SiO2=0.05;
[0163] H2O / SiO2=40;
[0164] The final mixture was charged into a stainless steel reactor and heated for crystallization at 145°C for 10 days under static crystallization conditions. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0165] The X-ray diffraction pattern of the molecular sieve sample is as follows Figure 7 As shown, the molecular sieve sample can be obtained as ZSM-48 molecular sieve;
[0166] SEM images of molecular sieve samples at different magnifications are shown below: Figure 8 As shown, the molecular sieve sample has an elliptical nanosheet morphology formed by the aggregation of nanoparticles, and the specific nanosheet cross morphology, the nanoparticles have a length of 35nm, a thickness of 35nm, a length of 800nm, a width of 460nm, an aspect ratio of 22.9, and an aspect ratio of 1.7;
[0167] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was 171 measured by inductively coupled plasma atomic emission spectroscopy (ICP);
[0168] N2 physical adsorption diagram of molecular sieve samples and Figure 3 Similarly, the specific surface area of molecular sieve is 312 m 2 / g, the external specific surface area measured by BET method is 156 m 2 / g; total pore volume 0.37 cm 3 / g, micropore volume is 0.07 cm 3 / gram.
[0169] The molecular sieve sample was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for 3 hours, centrifuged and washed, and the above steps were repeated twice, then dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain hydrogen-type ZSM-48 molecular sieve;
[0170] NH3-TPD diagram of hydrogen-type ZSM-48 molecular sieve Figure 4 Similarly, it can be obtained that the total acid content of the molecular sieve sample is 234 μmol / g, the strong acid content is 61 μmol / g, and the proportion of the strong acid content to the total acid content is 26%.
[0171] Hydroisomerization reaction was carried out using hydrogen-type ZSM-48 molecular sieve, the catalyst loading was 0.4 g, the particle size was 20-40 mesh, the molar ratio of hydrogen to n-heptane was 26, the reaction temperature was 200-400 °C, and the weight hourly space velocity was 1 h-1 In the temperature range of 280-320°C, the yield of the isomer product reached a maximum of 59%.
[0172] Example 6
[0173] The method of Example 1 is followed, except that 1.35 g of ethyl orthosilicate is replaced with silica sol (40% mass concentration), and the mass of the silica sol is controlled so that the molar ratio of the final mixture is:
[0174] SiO2 / Al2O3=61;
[0175] NaOH / SiO2=0.35;
[0176] SDA / SiO2=0.05;
[0177] H2O / SiO2=40;
[0178] The final mixture was charged into a stainless steel reactor and heated for crystallization at 150°C for 5 days under static crystallization conditions. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0179] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample can be obtained as ZSM-48 molecular sieve;
[0180] SEM images of molecular sieve samples and Figure 2 Similarly, it can be obtained that the molecular sieve sample has an elliptical nanosheet morphology formed by the aggregation of nanoparticles, and the specific nanosheet cross morphology, the length of the nanoparticle is 40nm, the thickness of the nanosheet is 18nm, the length is 430nm, the width is 320nm, the aspect ratio is 23.9, and the aspect ratio is 1.3;
[0181] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was measured to be 64 by inductively coupled plasma atomic emission spectroscopy (ICP);
[0182] The N2 physical adsorption diagram of the molecular sieve sample is as follows Figure 3 As shown, the specific surface area of the molecular sieve is 321 m 2 / g, the external specific surface area measured by BET method is 159 m 2 / g; total pore volume 0.39 cm 3 / g, micropore volume is 0.07 cm 3 / gram.
[0183] The molecular sieve sample was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for 3 hours, centrifuged and washed, and the above steps were repeated twice, then dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain hydrogen-type ZSM-48 molecular sieve;
[0184] NH3-TPD diagram of hydrogen-type ZSM-48 molecular sieve Figure 4 Similarly, it can be obtained that the total acid content of the molecular sieve sample is 712 μmol / g, the strong acid content is 236 μmol / g, and the proportion of the strong acid content to the total acid content is 33%.
[0185] Hydroisomerization reaction was carried out using hydrogen-type ZSM-48 molecular sieve, the catalyst loading was 0.4 g, the particle size was 20-40 mesh, the molar ratio of hydrogen to n-heptane was 26, the reaction temperature was 200-400 °C, and the weight hourly space velocity was 1 h -1 In the temperature range of 280-320°C, the yield of the isomer product reaches a maximum of 70%.
[0186] Example 7
[0187] The method of Example 4 is followed, except that white carbon black is used to replace 1.50 g of ethyl orthosilicate, and the mass of the white carbon black is controlled so that the molar ratio of the final mixture is:
[0188] SiO2 / Al2O3=59;
[0189] NaOH / SiO2=0.36;
[0190] SDA / SiO2=0.07;
[0191] H2O / SiO2=41;
[0192] The final mixture was charged into a stainless steel reactor and heated for crystallization at 150°C for 4 days under static crystallization conditions. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0193] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample can be obtained as ZSM-48 molecular sieve;
[0194] SEM images of molecular sieve samples and Figure 2 Similarly, it can be obtained that the molecular sieve sample has an elliptical nanosheet morphology formed by the aggregation of nanoparticles, and the specific nanosheet cross morphology, the length of the nanoparticle is 25nm, the thickness of the nanosheet is 20nm, the length is 460nm, the width is 280nm, the aspect ratio is 23.0, and the aspect ratio is 1.6;
[0195] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was measured to be 65 by inductively coupled plasma atomic emission spectroscopy (ICP);
[0196] N2 physical adsorption diagram of molecular sieve samples and Figure 3 Similarly, the specific surface area of molecular sieve is 346 m 2 / g, the external specific surface area measured by BET method is 149 m 2 / g; total pore volume 0.40 cm 3 / g, micropore volume is 0.08 cm 3 / gram.
[0197] The molecular sieve sample was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for 3 hours, centrifuged and washed, and the above steps were repeated twice, then dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain hydrogen-type ZSM-48 molecular sieve;
[0198] NH3-TPD diagram of hydrogen-type ZSM-48 molecular sieve Figure 4 Similarly, it can be obtained that the total acid content of the molecular sieve sample is 489 μmol / g, the strong acid content is 202 μmol / g, and the proportion of the strong acid content to the total acid content is 41%.
[0199] Hydroisomerization reaction was carried out using hydrogen-type ZSM-48 molecular sieve, the catalyst loading was 0.4 g, the particle size was 20-40 mesh, the molar ratio of hydrogen to n-heptane was 26, the reaction temperature was 200-400 °C, and the weight hourly space velocity was 1 h -1 In the temperature range of 280-320°C, the yield of the isomer product reached a maximum of 67%.
[0200] Example 8
[0201] The method of Example 4 is followed, except that potassium hydroxide is used to replace 0.10 g of sodium hydroxide, and the mass of potassium hydroxide is controlled so that the molar ratio of the final mixture is:
[0202] SiO2 / Al2O3=59;
[0203] KOH / SiO2=0.36;
[0204] SDA / SiO2=0.07;
[0205] H2O / SiO2=41;
[0206] The final mixture was charged into a stainless steel reactor and heated for crystallization at 150°C for 4 days under static crystallization conditions. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0207] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample can be obtained as ZSM-48 molecular sieve;
[0208] SEM images of molecular sieve samples and Figure 2 Similarly, it can be obtained that the molecular sieve sample has an elliptical nanosheet morphology formed by the aggregation of nanoparticles, and the specific nanosheet cross morphology, the length of the nanoparticle is 20nm, the thickness of the nanosheet is 16nm, the length is 370nm, the width is 200nm, the aspect ratio is 23.1, and the aspect ratio is 1.9;
[0209] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was measured to be 53 by inductively coupled plasma atomic emission spectroscopy (ICP);
[0210] N2 physical adsorption diagram of molecular sieve samples and Figure 3 Similarly, the specific surface area of molecular sieve is 311 m 2 / g, the external specific surface area measured by BET method is 146 m 2 / g; total pore volume 0.42 cm 3 / g, micropore volume is 0.08 cm 3 / gram.
[0211] The molecular sieve sample was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for 3 hours, centrifuged and washed, and the above steps were repeated twice, then dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain hydrogen-type ZSM-48 molecular sieve;
[0212] NH3-TPD diagram of hydrogen-type ZSM-48 molecular sieve Figure 4 Similarly, it can be obtained that the total acid content of the molecular sieve sample is 596 μmol / g, the strong acid content is 186 μmol / g, and the proportion of the strong acid content to the total acid content is 31%.
[0213] Hydroisomerization reaction was carried out using hydrogen-type ZSM-48 molecular sieve, the catalyst loading was 0.4 g, the particle size was 20-40 mesh, the molar ratio of hydrogen to n-heptane was 26, the reaction temperature was 200-400 °C, and the weight hourly space velocity was 1 h -1 In the temperature range of 280-320°C, the yield of the isomer product reached a maximum of 68%.
[0214] Comparative Example 1
[0215] The method of Example 4 is followed, except that 1,6-hexanediamine is used as the structure directing agent, and the mass of 1,6-hexanediamine is controlled so that the molar ratio of the final mixture is:
[0216] SiO2 / Al2O3=59;
[0217] NaOH / SiO2=0.36;
[0218] SDA / SiO2=0.07;
[0219] H2O / SiO2=41;
[0220] The final mixture was placed in a stainless steel reactor and heated for crystallization at 150°C for 4 days. After crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample. Figure 1 Similarly, it can be obtained that the molecular sieve sample is ZSM-48 molecular sieve; the SEM image of the molecular sieve sample is as follows Fig. 9 As shown, it has a rod-like morphology, not a nanosheet-like morphology.
[0221] The molecular sieve sample was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for 3 hours, centrifuged and washed, and the above steps were repeated twice. It was then dried at 100°C overnight and calcined in air at 550°C for 4 hours to obtain the hydrogenated ZSM-48 molecular sieve.
[0222] Hydroisomerization reaction was carried out using hydrogen-type ZSM-48 molecular sieve, the catalyst loading was 0.4 g, the particle size was 20-40 mesh, the molar ratio of hydrogen to n-heptane was 26, the reaction temperature was 200-400 °C, and the weight hourly space velocity was 1 h -1 In the temperature range of 280-320°C, the yield of the isomer product reached a maximum of 41%.
[0223] It can be seen from the results of the above examples and comparative examples that the isomerization reaction using the nanosheet ZSM-48 molecular sieve of the specific morphology of the present invention in Examples 1-8 has a significantly better yield of isomers than the rod-shaped ZSM-48 molecular sieve of Comparative Example 1.
[0224] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A nano-flaky ZSM-48 molecular sieve, characterized in that: The molecular sieve has a nanosheet morphology formed by agglomeration of nanoparticles, the length of the nanoparticles is not higher than 50 nm, and the length of the nanosheet is not higher than 1000 nm.
2. The molecular sieve according to claim 1, wherein The length of the nanoparticles is 10-50 nm, preferably 15-45 nm; and / or The molecular sieve has a morphology of intersecting nanosheets; and / or The nanosheets are elliptical nanosheets.
3. The molecular sieve according to claim 1 or 2, wherein: The length of the nanosheet is 300-900 nm, preferably 300-800 nm; and / or The thickness of the nanosheet is 10-100 nm, preferably 10-80 nm; and / or The width of the nanosheet is 200-800nm, preferably 200-700nm; Preferably, The aspect ratio of the nanosheet is 1-2, preferably 1.1-1.9; and / or The aspect ratio of the nanosheet is 5-30, preferably 5-25.
4. The molecular sieve according to any one of claims 1 to 3, wherein: The SiO2 / Al2O3 molar ratio of the molecular sieve is 40-250, preferably 50-240; and / or The total specific surface area of the molecular sieve is not less than 300 m 2 / g, preferably 300-500 m 2 / g; and / or The external specific surface area of the molecular sieve is not less than 100 m 2 / g, preferably 100-250 m 2 / gram.
5. The molecular sieve according to any one of claims 1 to 4, wherein: The total pore volume of the molecular sieve is not less than 0.25 cm 3 / g, preferably 0.25-0.6 cm 3 / g; and / or The micropore volume of the molecular sieve is not less than 0.05 cm 3 / g, preferably 0.05-0.2 cm 3 / gram.
6. The method for preparing the ZSM-48 molecular sieve according to any one of claims 1 to 5, characterized in that: The preparation method comprises: A mixed solution formed by a silicon source, an aluminum source, a structure directing agent and an alkali source raw material is subjected to a heating crystallization treatment; Wherein, the structure directing agent is composed of the structural unit a shown in formula (1), In formula (1), X is halogen or OH, and * represents a bonding site.
7. The preparation method according to claim 6, wherein: The average degree of polymerization of the structure directing agent is 2-20, preferably 3-12; and / or The silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, the structure directing agent is calculated as structural unit a, and the alkali source is calculated as cation. The molar ratio of the silicon source, the aluminum source, the structure directing agent, the alkali source and the water in the mixture is 1:a:b:c:d, wherein a is 0.004-0.03, b is 0.03-0.1, c is 0.10-0.5, and d is 8-100; Preferably, a is 0.004-0.025; and / or b is 0.04-0.09; and / or c is 0.15-0.45; and / or d is 10-90.
8. The preparation method according to claim 6 or 7, wherein: The crystallization conditions include: crystallization at 130-190° C. for 2-14 days, preferably crystallization at 140-180° C. for 3-12 days; and / or After the crystallization treatment, solid-liquid separation and heat treatment are performed; The heat treatment conditions include: calcination after drying, preferably the calcination conditions include: calcination temperature of 300-800° C.; and / or calcination time of 1-10 hours; and / or calcination in an oxygen-containing atmosphere.
9. Use of the ZSM-48 molecular sieve according to any one of claims 1 to 5 in adsorption treatment and / or organic compound conversion reaction.
10. A method for preparing hydrogen-type ZSM-48 molecular sieve, characterized in that: The preparation method comprises: The ZSM-48 molecular sieve described in any one of claims 1 to 5 is subjected to ammonium exchange, solid-liquid separation, and then heat treatment to obtain the hydrogen-type ZSM-48 molecular sieve.
11. The hydrogen-type ZSM-48 molecular sieve prepared by the preparation method according to claim 10; Preferably, the total acid content of the hydrogen ZSM-48 molecular sieve is not less than 150 μmol / g, preferably 150-1000 μmol / g; and / or The strong acid content of the hydrogen ZSM-48 molecular sieve is not less than 70 μmol / g, preferably 70-500 μmol / g; and / or The proportion of the strong acid content of the hydrogen-type ZSM-48 molecular sieve to the total acid content is not less than 25%, preferably 25-50%.
12. Use of the hydrogen-type ZSM-48 molecular sieve according to claim 11 in adsorption treatment and / or organic compound conversion reaction.
Citation Information
Patent Citations
ZSM-48 molecular sieve and preparation method thereof
CN111137905A
Synthesis method and application of ZSM-48 molecular sieve with low silica-alumina ratio
CN114436289A
Preparation method of hierarchical pore MRE molecular sieve
CN115072737A
MFI with unusual morphology
WO2014082862A1
